Hyper fibrinolysis state in COVID 19 and its correlation to lipid parameters - Abhilash Sharma; Anupama Hegde; M. Nandini; K. Sowndarya; M.S. Rukmini; K. Ashok Prabhu (Elsevier, 2024)
Background: Coronavirus disease 2019 (COVID 19) is associated with systemic effects involving especially the respiratory and cardiovascular system. The unique features of this condition are disseminated intravascular coagulation, excess fibrin degradation products due to abnormality in the coagulation system that could independently predict mortality. Abberations in lipid parameters that normally predict cardiovascular disease (CVD) were compared with D-dimer levels as risk markers in patients with COVID 19. Methods: A hospital based cross sectional study was conducted over a period of five months in patients aged 30-70 years diagnosed with COVID-19. The patients were categorised based on the D-dimer levels as: Group I < 0.5 μg/ml (Normal), Group II 0.5-2.0 μg/ml (Intermediate high), Group III >2.0 μg/ml (Very high). The lipid parameters, atherogenic indices were compared between the three groups. Results: The mean age of the selected COVID-19 patients was 49.3 ± 19.1 years of which 63 were males and 37 females (2:1). Significantly high D-dimer levels were detected which had a weak positive correlation with TG, Atherogenic Index Plasma (AIP). Significant rise in TC, LDL and Non-HDL was seen in Group II. Increasing trend of AIP was seen across the groups. D-dimer showed a weak positive correlation with TG, AIP and statistically non-significant negative correlation with rest of the lipid parameters. Conclusion: Though an overall increase in D-dimer, TG and AIP was observed in COVID-19 patients, categorization based on D-dimer status detected lowering LDL and increasing AIP on deterioration of disease state.